Identification of simple sequence repeat markers linked to heat tolerance in rice using bulked segregant analysis in F2 population of NERICA-L 44 × Uma - Stephen, K.; Aparna, K.; Beena, R.; Sah, R. P.; Jha, Uday Chand; Behera, Sasmita (Frontiers in Plant Science, 2023)
The present investigation was undertaken to identify polymorphic microsatellite markers (SSR) associated with heat tolerance. The rice cultivars NERICA– L 44 (heat tolerant) and Uma (heat susceptible) were crossed to generate F1 and F2 populations. The F2 population was subjected to heat stress at >38 ˚C and the 144 F2 plants were evaluated for their tolerance. The results note that the mean of the F2 population was influenced by the tolerant parent with regards to the traits of plant height, membrane stability index, photosynthetic rate, stomatal conductance, evapotranspiration rate, pollen viability, spikelet fertility and 1000 grain weight. Ten each of the extremely susceptible and tolerant plants were selected based on the spikelet fertility percentage. Their DNA was pooled into tolerant and susceptible bulks and Bulked Segregant Analysis (BSA) was carried out using 100 SSR markers to check for polymorphism. The survey revealed a polymorphism of 18% between the parents. RM337, RM10793, RM242, RM5749, RM6100, RM490, RM470, RM473, RM222 and RM556 are some of the prominent markers that were found to be polymorphic between the parents and the bulks. We performed gene annotation and enrichment analysis of identified polymorphic markers. Result revealed that the sequence specific site of that chromosome mostly enriched with biological processes like metabolic pathway, molecular mechanism, and subcellular function. Among that RM337 was newly reported marker for heat tolerance. Expression analysis of two genes corresponds to RM337 revealed that LOP1 (LOC_Os08g01330) was linked to high temperature tolerance in rice. The results demonstrate that BSA using SSR markers is useful in identifying genomic regions that contribute to thermo-tolerance.